Investigating the Effects of Several Variables on University Students' Social Media Addiction - Demir, Yasin; Kumcağız, Hatice (Turkish Psychological Counseling and Guidance Association, 2019)
The aim of the study is to analyze social media addiction of university students in terms of several variables. The study sample consisted of a total of 374 students, 194 of whom were female (52%), and 180 of whom were male (48%). The students are studying at different departments at Ondokuz Mayıs University, Education Faculty. The data was collected with a Social Media Addiction Scale - Adult Form and personal information form. In the data analysis, SPSS was used percentage, frequency, t-test, one-way variance analysis (ANOVA) and Scheffe difference tests. According to the study results, it was revealed that the participant students' social media addiction did not differ in terms of gender. The students with higher academic success had a lower level of social media addiction. The students who spent a lot of time on social media and the ones who made use of it for downloading video/music were found to possess higher level of social media addiction. Also, it was found that the participants who expressed that they are harmed from social media use are si nificantl hi her than those who ex ressed the are unharmed The results were discussed in the light of the literature and some suggestions were made. © 2019 The Author(s).
Üniversite Öğrencilerinin Sosyal Medya Bağımlılığının Farklı Değişkenler Açısından İncelenmesi
Keywords: Social media; social media addiction university students